“Work of Kinship” done by Families in Santiago de Chile - Gonzálvez Torralbo, Herminia (Revista de Antropología Social, 2016)
This paper reports the progress achieved in an anthropological investigation based on which there is now a more in depth understanding of some dimensions of the “kinship work” carried out by families in Chile. The main objective is to analyze the work of maintaining family links performed primarily by women within families and show how this work reproduces gender inequalities within them. On the basis of a longitudinal methodology based on semi-structured interviews, it is concluded that the work of maintaining family links performed by women is crucial but goes unnoticed because kinship obligations are seen as a naturally being part of women’s role in the family.
Keywords: Kinship Work; family links; Chile; care.